Elastography in Hepatology - Ludovico Abenavoli; Christophe Corpechot; Raoul Poupon (Canadian Journal of Gastroenterology)
A common characteristic of all chronic liver diseases is the occurrence and progression of fibrosis toward cirrhosis. Consequently, liver fibrosis assessment plays an important role in hepatology. Besides its importance for prognosis, determining the level of fibrosis reveals the natural history of the disease and the risk factors associated with its progression, to guide the antifibrotic action of different treatments. Currently, in clinical practice, there are three available methods for the evaluation of liver fibrosis: liver biopsy, which is still considered to be the ‘gold standard’; serological markers of fibrosis and their mathematical combination – suggested in recent years to be an alternative to liver biopsy – and, more recently, transient elastography (TE). TE is a new, simple and noninvasive method used to measure liver stiffness. This technique is based on the progressing speed of an elastic shear wave within the liver. Currently, there are only a few studies that have evaluated TE effectiveness in chronic liver diseases, mostly in patients infected with the hepatitis C virus. Further studies are needed in patients with chronic liver disease, to assess the effectiveness of the fibrosis treatment.